Research approaches in examining M-Government Services: an investigation / Noor Suriana Abu Bakar ... [et al.] - Abu Bakar, Noor Suriana; Abdul Rahman, Azizah; Abdul Hamid, Haza Nuzly (2014)
Mobile government, which is an emergent phenomenon, represents a solution for many countries to reach their citizens and to improve the services of government-to-citizens (G2C). Hence, most researchers have merely focused on the citizens’ adoption and usage issues, security, implementation and transformation, and the success factors of m-government services. However, in order to proceed with the study on examining the m-government services, it is vital to first analyze the most suitable research method that can be used. Thus, this paper investigated the research approaches used for examining m-government services by reviewing 37 papers that are related to this topic, which were retrieved from four online databases: a) IEEE Xplore, b) Science Direct, c) Emerald, and d) ACM Digital Library. Only papers from 2007 to 2014 were selected for further review. The findings suggested that the survey method was mostly used to examine the m-government services.